2012
DOI: 10.5935/1808-8694.20120017
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of β-hemolytic Streptococcus in children with special health care needs

Abstract: The early identification of β-hemolytic Streptococcus is important for the fast treatment of pharyngotonsillitis and the absence of S. pyogenes avoid future suppurative or not-suppurative sequels in the group from APAE.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 16 publications
0
6
0
Order By: Relevance
“…Omurzakova et al (11) compared rapid antigen detection test with bacterial culture analysis and, bacterial culture analysis were observed to be more sensitive test. Morais et al (12) reported that the prevalence of GAS were 7.7% (5/65) in the students from a private school. In the performed throat culture study between 1998-2002 years, the percentages of GAS-positive throat cultures were observed between 13,4% to 17,7% according to study year (13).…”
Section: Discussionmentioning
confidence: 99%
“…Omurzakova et al (11) compared rapid antigen detection test with bacterial culture analysis and, bacterial culture analysis were observed to be more sensitive test. Morais et al (12) reported that the prevalence of GAS were 7.7% (5/65) in the students from a private school. In the performed throat culture study between 1998-2002 years, the percentages of GAS-positive throat cultures were observed between 13,4% to 17,7% according to study year (13).…”
Section: Discussionmentioning
confidence: 99%
“…To the best of our knowledge this is the first case report of neonatal meningitis due to Streptococcus bovis in a child with Down syndrome. Previous reports have shown that children with Down syndrome have intrinsic defects in the immune system and are at higher risk of developing infections due to streptococcal organisms [ 8 , 9 ]. Abnormalities in the immune system associated with Down syndrome include reduced T lymphocyte and B lymphocyte counts, absence of normal lymphocyte expansion in infancy, impaired mitogen-induced T cell proliferation, reduced specific antibody responses to immunizations, and defects of neutrophil chemotaxis [ 10 ].…”
Section: Discussionmentioning
confidence: 99%
“…Omurzakova et al (2010) compared to rapid antigen detection test and bacterial culture analysis, bacterial culture analysis were observed to be more sensitive test. Morais et al (2012) reported that the prevalence of GAS were 7.7% (5/65) in the students from a private school. In the performed throat culture study between 1998-2002 years, the percentages of GASPositive throat cultures were observed between 13.4% to 17.7% according to study year (Martin et al, 2004).…”
Section: Discussionmentioning
confidence: 99%